Binder for coating lithium battery current collector and preparation method thereof
By using adhesives prepared by polyvinylidene fluoride, maleic anhydride graft modified styrene-ethylene/butene-styrene and other materials on the lithium battery current collector, the problems of low tensile strength and easy breakage of the current collector copper foil are solved, and better adhesiveness and electrolyte resistance are achieved.
Patent Information
- Application Number
- CN202411947946.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing lithium battery current collector copper foil has problems such as low tensile strength, poor coating continuity, easy breakage, easy folding of copper foil and reduced yield.
A binder for coating of lithium battery current collectors, including polyvinylidene fluoride, maleic anhydride graft modified styrene-ethylene/butene-styrene, modified polyolefin, ceramic powder, coupling agent, antioxidant and solvent, is uniformly prepared by heating, dissolving, stirring and mixing.
This adhesive has good adhesion to the current collector copper foil and aluminum foil, is resistant to electrolyte corrosion, improves the tensile strength of the current collector breaking, effectively protects the current collector, and improves the feasibility of industrial utilization.
Smart Images

Figure BDA0005214162580000061 
Figure BDA0005214162580000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives for lithium batteries, and in particular to an adhesive for coating a lithium battery current collector and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are rechargeable batteries. Due to their high operating voltage, compact size, lightweight, high energy content, lack of memory effect, low self-discharge, long cycle life, and high capacity per unit density, they are widely used in mobile phones, laptops, wearable electronic devices, power tools, drones, and electric vehicles. Existing lithium-ion battery positive tabs typically use aluminum tabs (or other metals and alloys) with aluminum foil as the current collector; negative tabs use nickel tabs (or other metals and alloys) with copper foil as the current collector. The tabs are connected to the current collector using welding methods (super welding, riveting, etc.). The ultra-thin current collector copper foil presents a series of problems: low tensile strength, poor coating continuity, and susceptibility to breakage; thinner copper foil increases the tendency for the tabs to fold inward, reducing yield; and burrs on the cut edges of the copper foil. Summary of the Invention
[0003] The present invention addresses the deficiencies of existing lithium battery current collectors and aims to provide a binder for coating lithium battery current collectors and a preparation method thereof.
[0004] In order to achieve the above objectives, the technical solutions adopted are:
[0005] One of the objects of the present invention is to provide a binder for coating a lithium battery current collector, which comprises the following components, in parts by weight: 10 to 20 parts of polyvinylidene fluoride, 10 to 20 parts of maleic anhydride grafted modified styrene-ethylene / butylene-styrene, 1 to 10 parts of modified polyolefin, 50 to 70 parts of ceramic powder, 0.1 to 1 part of a coupling agent, 0.1 to 3 parts of an antioxidant, and 300 to 500 parts of a solvent.
[0006] The polyvinylidene fluoride (PVDF), PVDF homopolymer and copolymer with a weight average molecular weight of 500,000 to 1.1 million, can be produced by Solvay. Kynar HSV 1800 / 900 produced by Arkema, the polyvinylidene fluoride (PVDF) has the properties of anti-aging, chemical resistance, weather resistance, and ultraviolet radiation resistance, is chemically inert and does not react with electrolytes or lithium.
[0007] Furthermore, the maleic anhydride-grafted modified styrene-ethylene / butylene-styrene (SEBS-g-MAH) can be selected with a styrene content of 13% to 30% by weight and a maleic anhydride grafting ratio of 0.5% to 3.0%. Examples of SEBS include Asahi Kasei TUFTEC M1911 and TUFTEC M1941 from Japan, and Kraton FG1901 and FG1924 from the United States. This maleic anhydride-grafted modified styrene-ethylene / butylene-styrene is a polar thermoplastic elastomer with excellent compatibility and low-temperature flexibility. It can be used as a compatibilizer and adhesive for various engineering plastics, enhancing adhesion to metal substrates.
[0008] Furthermore, the modified polyolefin is polyethylene, polypropylene, or ethylene-propylene-1-butene copolymer modified with chlorine, carboxyl, anhydride, or amino. The modified polyolefin contains an unsaturated carboxylic acid component. From the perspective of obtaining a better adhesion to the current collector material, acrylic acid, methacrylic acid, maleic acid, and maleic anhydride are preferred, and acrylic acid and maleic anhydride are particularly preferred. The unsaturated carboxylic acid component in the modified polyolefin is contained by random copolymerization, block copolymerization, graft copolymerization (graft modification), etc. The mass content of the unsaturated carboxylic acid component in the modified polyolefin is 0.1% to 5%, preferably 0.8% to 3%. If the content of the unsaturated carboxylic acid component in the modified polyolefin is less than 0.1%, the adhesion to the metal substrate is low. If the content of the unsaturated carboxylic acid component in the modified polyolefin is greater than 5%, the water resistance deteriorates and the electrolyte resistance is reduced. Ethylene-ethyl acrylate-maleic anhydride copolymer (BONDINE HX-8290 or LX-4110 manufactured by Arkem) or maleic anhydride modified polypropylene resin (Orevac 18722 or Orevac 18751 manufactured by Arkem) can be used, or amorphous α-polyolefin Vestoplast 308 manufactured by Evonik or ADMER manufactured by Mitsui can be used. TM , a modified polyolefin composed of modified polyethylene and modified polypropylene, can act as a coupling agent to increase the compatibility between fillers and polyolefins.
[0009] Furthermore, the ceramic powder is at least one of high-purity alumina and boehmite, with the high-purity alumina having a purity of 99.99% or higher and a particle size D50 of 0.1 to 1.0 μm. Submicron boehmite (brand: LSB-2-2L) produced by China Aluminum Corporation Zhengzhou Nonferrous Metals Research Institute Co., Ltd. can be used, with a particle size D50 of 0.5 to 0.8 μm. High-purity alumina ZTL-WAO-030 produced by Yangzhou Zhongtianli can also be used, with a particle size D50 ≤ 1.0 μm. The addition of ceramic powder helps improve the heat resistance of the adhesive and also facilitates heat conduction, thereby resolving the problem of poor thermal conductivity of the adhesive.
[0010] Furthermore, the coupling agent is a titanate coupling agent or the like.
[0011] Furthermore, the antioxidant is a hindered phenol and phosphite composite antioxidant.
[0012] Furthermore, the solvent is N-methylpyrrolidone.
[0013] A second object of the present invention is to provide a method for preparing the binder for coating a lithium battery current collector, comprising the following steps:
[0014] In a reaction container, polyvinylidene fluoride, maleic anhydride grafted modified styrene-ethylene / butylene-styrene, modified polyolefin, ceramic powder, coupling agent, antioxidant, and solvent are added according to their mass parts, the temperature is raised to 60-80° C., the mixture is dissolved and stirred to mix evenly, and the mixture in the reaction container is cooled to room temperature to obtain the binder for coating the lithium battery current collector.
[0015] Compared with the prior art, the beneficial effect of the present invention is that the present invention combines the properties of polyvinylidene fluoride, maleic anhydride grafted modified styrene-ethylene / butylene-styrene and modified polyolefins, and the resulting adhesive has excellent adhesion to the current collector copper foil and aluminum foil, is resistant to electrolyte corrosion, and improves the current collector's tensile strength at break. DETAILED DESCRIPTION
[0016] The present invention is described below with reference to examples, which are only used to explain the present invention and are not used to limit the scope of the present invention.
[0017] Example 1
[0018] The process of coating a current collector of a lithium battery with a binder comprises the following steps:
[0019] In a 100L glass reactor equipped with an oil bath heater and a stirring device, 80kg of N-methylpyrrolidone (NMP) was added as solvent and heated to 70°C. 13kg of ceramic powder, submicron boehmite (brand: LSB-2-2L) produced by Zhengzhou Nonferrous Metals Research Institute Co., Ltd. of China Aluminum Corporation, and 3kg of polyvinylidene fluoride (PVDF) produced by Solvay were added in sequence. 5130; add 3 kg of maleic anhydride grafted modified styrene-ethylene / butylene-styrene, Kraton FG1901 from the United States; add 0.8 kg of modified polyolefin resin, BONDINE HX-8290 produced by Arkema; add 0.13 kg of coupling agent, titanate coupling agent TTS produced by Ajinomoto; add 0.5 kg of antioxidant, IRGANOX B215 produced by BASF; stir the solvent thoroughly for 3 hours, cool to room temperature, and obtain a binder with a solid content of 20%.
[0020] In Example 2, the ceramic powder used was high-purity alumina ZTL-WAO-030 produced by Yangzhou Zhongtianli, and the rest was the same as in Example 1.
[0021] Example 3: Kynar HSV 900 produced by Arkema was used as polyvinylidene fluoride, and other aspects were the same as those in Example 1.
[0022] Example 4 Maleic anhydride grafted modified styrene-ethylene / butylene-styrene used TUFTEC M1911 produced by Asahi Chemical Industry Co., Ltd., and other aspects were the same as those in Example 1.
[0023] Example 5: The modified polyolefin used is LX-4110 produced by Arkema, and the rest is the same as Example 1.
[0024] Comparative Example 1
[0025] To a 100 L glass reactor equipped with an oil bath heater and a stirrer, 80 kg of N-methylpyrrolidone (NMP) solvent was added and heated to 70° C. The mixture was then heated to 70° C., followed by the addition of 13 kg of ceramic powder (submicron boehmite, LSB-2-2L, manufactured by Aluminum Corporation of China, Zhengzhou Nonferrous Metals Research Institute Co., Ltd.); 3 kg of maleic anhydride-grafted modified styrene-ethylene / butylene-styrene (Kraton FG1901, USA); 0.8 kg of modified polyolefin resin (BONDINE HX-8290, manufactured by Arkema); 0.13 kg of coupling agent (titanate coupling agent TTS, manufactured by Ajinomoto); and 0.5 kg of antioxidant (IRGANOX B215, manufactured by BASF). The solvent was stirred thoroughly for 3 hours and cooled to room temperature to obtain a binder having a solids content of 20%.
[0026] Comparative Example 2
[0027] In a 100L glass reactor equipped with an oil bath heater and a stirring device, 80kg of N-methylpyrrolidone (NMP) was added as solvent and heated to 70°C. 13kg of ceramic powder, submicron boehmite (brand: LSB-2-2L) produced by Zhengzhou Nonferrous Metals Research Institute Co., Ltd. of China Aluminum Corporation, and 3kg of polyvinylidene fluoride (PVDF) produced by Solvay were added in sequence. 5130; add 0.8 kg of modified polyolefin resin, BONDINE HX-8290 produced by Arkema; add 0.13 kg of coupling agent, titanate coupling agent TTS produced by Ajinomoto; add 0.5 kg of antioxidant, IRGANOX B215 produced by BASF; stir the solvent thoroughly for 3 hours, cool to room temperature, and obtain a binder with a solid content of 20%.
[0028] Comparative Example 3
[0029] In a 100L glass reactor equipped with an oil bath heater and a stirring device, 80kg of N-methylpyrrolidone (NMP) was added as solvent and heated to 70°C. 13kg of ceramic powder, submicron boehmite (brand: LSB-2-2L) produced by Zhengzhou Nonferrous Metals Research Institute Co., Ltd. of China Aluminum Corporation, and 3kg of polyvinylidene fluoride (PVDF) produced by Solvay were added in sequence. 5130; add 3kg of maleic anhydride grafted modified styrene-ethylene / butylene-styrene, Kraton FG1901 from the United States; add 0.13kg of coupling agent, titanate coupling agent TTS produced by Ajinomoto; add 0.5kg of antioxidant, IRGANOX B215 produced by BASF; stir the solvent thoroughly for 3 hours, cool to room temperature, and obtain a binder with a solid content of 20%.
[0030] Comparative Example 4
[0031] An equal amount of unmodified polyolefin Vestoplast 703 was used to replace BONDINE HX-8290, and the rest was the same as in Example 1.
[0032] Comparative Example 5
[0033] The modified polyolefin used was maleic anhydride grafted polypropylene wax Licocene PP MA 6452 produced by Clariant, replacing BONDINE HX-8290, with a grafting rate of 7%. Other aspects were the same as those in Example 1.
[0034] The performance of the binder for coating lithium battery current collectors of Examples 1-5 and Comparative Examples 1-5 was tested using the following method:
[0035] 1) Viscosity test: Use Brookfield viscometer, model TC550, water bath temperature control, CP-42# rotor to test viscosity at 25°C;
[0036] 2) Bond strength test: Bond strength test: Apply adhesive to a 6μm thick copper foil with a thickness of 10μm, adhere hot melt adhesive with tape, and perform peel strength test according to the national standard GB / T 2792-2014 method;
[0037] 3) Electrolyte Immersion Adhesion Strength Test: Immerse the sample from step 2) in lithium battery electrolyte at 85°C for 6 hours. The electrolyte mass ratio is as follows: EC / PC / DEC / EP = 30 / 10 / 30 / 30, and the mass ratio of 1M LiPF6 lithium salt is calculated as 12.5%. After cooling to room temperature, the peel strength test is performed according to the method described in the national standard GB / T 2792-2014;
[0038] 4) Swelling thickness change rate test: The sample thickness is 4-7mm. Soak it in electrolyte (85℃ for 14 days). After the aged electrolyte is cooled to room temperature, remove the sample from the electrolyte. After wiping the electrolyte on the sample surface with a dust-free cloth, measure the thickness with a vernier caliper and calculate the thickness change rate.
[0039] 5) Dissolution rate test: Weigh the mass change of the sample before and after aging, soak it in electrolyte (85℃ for 14 days), cool the aged electrolyte to room temperature, remove the sample from the electrolyte, wipe the electrolyte on the sample surface with a dust-free cloth, and then perform the weighing test.
[0040] Table 1. Properties of the binder for coating lithium battery current collectors obtained in Examples 1-5
[0041]
[0042] Table 2. Properties of the binder for coating lithium battery current collectors obtained in Comparative Examples 1-5
[0043]
[0044]
[0045] Note: a peel strength > 0.5 N / mm means the tape cannot tear the coating off the foil. The force tested is the adhesion between the tape and the hot melt adhesive coating.
[0046] The results shown in Tables 1 and 2 indicate that the adhesive properties and electrolyte resistance of Examples 1-5, as well as the adhesive strength and swelling and dissolution properties after electrolyte immersion, all meet customer requirements. Comparative Example 1, which omitted polyvinylidene fluoride, exhibited poor electrolyte swelling and dissolution resistance. Comparative Examples 2-4, which omitted maleic anhydride-grafted modified styrene-ethylene / butylene-styrene, modified polyolefin resin, and substituted unmodified polyolefin, respectively, exhibited poor metal adhesion and electrolyte resistance. Comparative Example 5, which used a polyolefin with a 7% grafting ratio, exhibited poor electrolyte resistance.
[0047] The adhesive provided by the present invention has excellent adhesion to the current collector copper foil and aluminum foil, is resistant to electrolyte corrosion, improves the tensile strength of the current collector, can effectively protect the current collector, and has feasibility for industrial utilization.
[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A binder for coating a lithium battery current collector, characterized in that: The invention comprises the following components in parts by weight: 10 to 20 parts of polyvinylidene fluoride, 10 to 20 parts of maleic anhydride grafted modified styrene-ethylene / butylene-styrene, 1 to 10 parts of modified polyolefin, 50 to 70 parts of ceramic powder, 0.1 to 1 part of coupling agent, 0.1 to 3 parts of antioxidant and 300 to 500 parts of solvent.
2. The binder for coating a lithium battery current collector according to claim 1, characterized in that: The polyvinylidene fluoride is a homopolymer or copolymer with a weight average molecular weight of 500,000 to 1.1 million.
3. The binder for coating a lithium battery current collector according to claim 1, characterized in that: The grafting rate of maleic anhydride in the maleic anhydride graft-modified styrene-ethylene / butylene-styrene is 0.5-2.0%.
4. The binder for coating a lithium battery current collector according to claim 1, characterized in that: The modified polyolefin is polyethylene, polypropylene, or ethylene-propylene-1-butene copolymer modified by chlorine, carboxyl, anhydride or amino.
5. The binder for coating a lithium battery current collector according to claim 1, characterized in that: The modified polyolefin contains unsaturated carboxylic acid components, and the mass content of the unsaturated carboxylic acid components is 0.1% to 5%.
6. The binder for coating a lithium battery current collector according to claim 1, characterized in that: The modified polyolefin is at least one of ethylene-ethyl acrylate-maleic anhydride copolymer, maleic anhydride modified polypropylene resin, and amorphous α-polyolefin.
7. The binder for coating a lithium battery current collector according to claim 6, characterized in that: The ceramic powder is at least one of high-purity alumina and boehmite, and the particle size D50 is 0.1-1.0 μm.
8. The binder for coating a lithium battery current collector according to claim 7, characterized in that: The coupling agent is a titanate coupling agent.
9. The binder for coating a lithium battery current collector according to claim 8, characterized in that: The antioxidant is a hindered phenol and phosphite composite antioxidant.
10. A method for preparing a binder for coating a lithium battery current collector according to any one of claims 1 to 9, characterized in that: The following steps are involved: In a reaction container, polyvinylidene fluoride, maleic anhydride grafted modified styrene-ethylene / butylene-styrene, modified polyolefin, ceramic powder, coupling agent, antioxidant, and solvent are added according to mass proportions, the temperature is raised to 60-80° C., the mixture is dissolved and stirred to mix evenly, and the mixture in the reaction container is cooled to room temperature to obtain the binder for coating the lithium battery current collector.
Citation Information
Patent Citations
Modified PVDF (polyvinylidene fluoride) film for solar battery back panel and preparation method of modified PVDF film
CN102604274A
Backsheet for rigid photovoltaic modules
CN102612432A
Low-temperature-resistant, ultraviolet-resistant and impact-resistant transparent fluorine-containing polymer film
CN117801444A
Binder for positive plate, preparation method of binder, positive plate and secondary battery
CN118099424A
High-heat-resistance binder for lithium ion battery diaphragm and preparation method of high-heat-resistance binder
CN118909570A